2019
DOI: 10.18061/bhac.v3i1.6575
|View full text |Cite
|
Sign up to set email alerts
|

Examining Student Wellness for the Development of Campus-Based Wellness Programs

Abstract: Background: Despite the many campus-based wellness programs and services offered through entities such as student services, many U.S. students lack the strategies, skills, or support systems to manage stress or change pre-existing behaviors, resulting in unhealthy behaviors and poor overall wellness. Since patterns developed during this time can form a solid foundation for future health behaviors, there is a need to develop and design wellness programs that stimulate positive health-behavior change.Aim: The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Furthermore, results showed differences in utilisation of support services based on gender, of those who attended extra tutorials, remedial and academic skills workshops, the majority were males, which supports previous findings that more male students engaged with staff for academic matters (Schreiber & Yu, 2016;Sontag-Padilla et al, 2016;Franzidis & Zinder, 2019). In examining factors of college students' use of mental health services, authors (Sontag-Padilla et al, 2016) found that psycho-social support, mentorship, and spiritual support were mostly attended by females.…”
Section: Engagement Phase Supportsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, results showed differences in utilisation of support services based on gender, of those who attended extra tutorials, remedial and academic skills workshops, the majority were males, which supports previous findings that more male students engaged with staff for academic matters (Schreiber & Yu, 2016;Sontag-Padilla et al, 2016;Franzidis & Zinder, 2019). In examining factors of college students' use of mental health services, authors (Sontag-Padilla et al, 2016) found that psycho-social support, mentorship, and spiritual support were mostly attended by females.…”
Section: Engagement Phase Supportsupporting
confidence: 75%
“…In examining factors of college students' use of mental health services, authors (Sontag-Padilla et al, 2016) found that psycho-social support, mentorship, and spiritual support were mostly attended by females. However, literature reveals that female students at HEIs receive inadequate family and social support, instead they are giving such support (Lin 2016), due to their higher social and emotional wellness compared to their male counterparts (Alexia & Steven, 2019;Franzidis & Zinder, 2019).…”
Section: Engagement Phase Supportmentioning
confidence: 99%
“…In order to identify strategies that will create healthy campuses and highlight the significance of health promotion and wellness in universities and colleges, studies recommend assessing first the health promotion behaviors and wellness of the students (Franzidis & Zinder, 2019;Kim & Kim, 2018;LaFountaine et al, 2007). Exploring students' health-promoting behaviors is essential for creating well-designed health promotion interventions that will enhance college students' quality of life.…”
Section: Introductionmentioning
confidence: 99%